الثقافة التنظيمية وعلاقتها بالولاء التنظيمي عند إطارات المؤسسة الوطنية سوناطراك - عشوش, بشير (Université de M'sila, 2017)
- الملخص: تناولنا في هذه الدراسة الثقافة التنظيمية من جهة باعتبارها مجموعة من القيم والمعتقدات والأعراف والتوقعات التي توجه سلوك المستخدمين، والتي تستمد من الثقافة الاجتماعية ومن رسالة المنظمة ورؤيتها وأهدافها، وهي بمثابة المرجع الذي يعود إليه المستخدمون لنهج السلوكات الايجابية داخل المنظمة، ومن جهة أخرى موضوع الولاء التنظيمي الذي يعد المفتاح الأساسي والمهم لتفحص مدى الانسجام القائم بين الأفراد ومنظماتهم، فالأفراد ذو الولاء التنظيمي المرتفع اتجاه منظماتهم هم الذين لديهم الاستعدادات الكافية لأن يكرسوا مزيدا من الجهد والتفاني في أعمالهم ويسعوا بصورة دائمة على استمرار ارتباطهم وانتمائهم لمنظمتهم (الشلوي، 2005). ومن بين الانعكاسات التي يولدها انعدام الولاء التنظيمي نجد الدوران في العمل والذي يعتبر حاجزا ومسألـــــة عويصة بالنسبة للمسيرين وخاصة عندما يتعلق الأمر بمستخدمين ذوي الكفاءات العالية. وقد توصلنا من خلال هذه الدراسة إلى وجود علاقة ارتباطية موجبة بين الثقافة التنظيمية والولاء التنظيمي لدى عينة الدراسة وهذا فيما يخص كل من بعد الأولوية للجماعة، الأهمية للأفراد، الإبداع وأحذ المخاطر، الانشغال بالتفاصيل في أداء المهام، المنافسة والاستقرار. أما بالنسبة لبعد التوجه نحو النتائج فكانت العلاقة ارتباطية سالبة. - الكلمات المفتاحية: الثقافة التنظيمية - الولاء التنظيمي الإطارات. -Abstract: We ate in the study of organizational culture on the one hand as a set of values and beliefs and norms and expectations that guide the behavior of users, and which derives from the social culture and the organization's mission and vision and objectives, and serves as a reference, which dates back to users to approach positive behaviors within the organization, and on the other hand, the subject of organizational loyalty, which is the primary key and it is important to examine the extent of the harmony that exists between individuals and their organizations, are the ones who have the adequate preparations because devote more effort and dedication in their work and seek permanently the continuation of their association and affiliation to their organization (Alchalwi, 2005). Among the reflections generated by the lack of organizational loyalty, we find circulation at work, which is a barrier and a difficult issue for managers, especially when it comes to user-based highly qualified. We have reached through this study to the existence of a positive correlation between organizational culture and Organizational loyalty among a sample study and this in respect of each of the later priority of the group, is important for individuals, creativity and grrisks, preoccupation with details on the performance of tasks, competition and stability. As for the post-results orientation was a negative correlation relationship.
Keywords: الثقافة التنظيمية - الولاء التنظيمي الإطارات. Organizational Culture - Organizational Loyalty – Executives.